Cleaning effectiveness of a nickel-titanium ultrasonic tip in ultrasonically activated irrigation: A SEM study - Bueno, Carlos Roberto Emerenciano [UNESP]; Cury, Marina Tolomei Sandoval [UNESP]; Vasques, Ana Maria Veiga [UNESP]; Sarmiento, Jimena Lama [UNESP]; Trizzi, Juliana Quintino [UNESP]; Jacinto, Rogério de Castilho [UNESP]; Araújo, Gustavo Sivieri de [UNESP]; Dezan Junior, Eloi [UNESP] (FapUNIFESP (SciELO), 2019)
In endodontic treatment, regardless of the instrumentation technique, the presence of a smear layer covering contaminated dentin walls is always a concern. Thus, irrigation plays an essential role in reducing bacterial load. To enhance irrigation effectiveness, different ultrasonic activation methods and the use of different tips have been studied. This study assessed the cleaning capacity of the novel NiTi ultrasonic tip for smear layer removal using ultrasonically activated irrigation (UAI) with passive or continuous ultrasonic irrigation (PUI or CUI, respectively), compared with conventional irrigation. Forty-five single-rooted human mandibular premolars were decoronated to a standardized length of 16 mm. Instrumentation was performed using the Genius system up to size 50.04 and irrigated with 3% NaOCl. The specimens were divided into three groups (n = 15) according to the final irrigation activation technique: conventional irrigation (CI), as control group; PUI; and CUI, following the manufacturer's protocol. The samples were longitudinally cleaved and analyzed under a scanning electron microscope for smear layer removal according to a cleanliness score for the cervical, middle, and apical thirds. Data were evaluated by means of the Kruskal-Wallis and Tukey's tests, with a 5% level of significance. UAI enhanced cleaning compared to conventional irrigation, mainly at the apical third. CUI showed the best results, with statistically significant lower scores than PUI and CI (p < 0.05). Final irrigant activation with the NiTi tip showed better cleaning capacity than conventional irrigation. In addition, CUI resulted in better smear layer removal than PUI.
Keywords: Dental Pulp Cavity; Endodontics; Instrumentation